2017
DOI: 10.1039/c6ra25859j
|View full text |Cite
|
Sign up to set email alerts
|

Beauveria bassiana (Clavicipitaceae): a potent fungal agent for controlling mosquito vectors of Anopheles stephensi, Culex quinquefasciatus and Aedes aegypti (Diptera: Culicidae)

Abstract: The efficacy of bioactive compounds identified from Beauveria bassiana extracts as effective larvicidal and pupicidal agents against Anopheles stephensi, Culex quinquefasciatus and Aedes aegypti mosquito vectors under laboratory conditions are studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 36 publications
(29 reference statements)
2
24
0
3
Order By: Relevance
“…demonstrated acute effects of B. bassiana on C. riparius first‐instar larvae at much higher concentrations (48‐h LC 50 34.7 mg L −1 ) than those found in this study (48‐h LC 50 6.35 μg L −1 ). Another study focused on other aquatic Dipteran larvae such as Anopheles stephensi , Culex quinquefasciatus and Aedes aegypti , reporting 24‐h LC 50 values ranging from 25.72 to 72.38 mg a.i./L, after exposure to B. bassiana , depending on the larval instar . Clark et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…demonstrated acute effects of B. bassiana on C. riparius first‐instar larvae at much higher concentrations (48‐h LC 50 34.7 mg L −1 ) than those found in this study (48‐h LC 50 6.35 μg L −1 ). Another study focused on other aquatic Dipteran larvae such as Anopheles stephensi , Culex quinquefasciatus and Aedes aegypti , reporting 24‐h LC 50 values ranging from 25.72 to 72.38 mg a.i./L, after exposure to B. bassiana , depending on the larval instar . Clark et al .…”
Section: Discussionmentioning
confidence: 99%
“…Another study focused on other aquatic Dipteran larvae such as Anopheles stephensi, Culex quinquefasciatus and Aedes aegypti, reporting 24-h LC 50 values ranging from 25.72 to 72.38 mg a.i./L, after exposure to B. bassiana, depending on the larval instar. 63 Clark et al 64 was the first study showing the different susceptibility of larval and adult stages of different mosquito species to B. bassiana. Bukhari et al 24 confirmed toxicity of B. bassiana toward A. stephensi and Anopheles gambiae larvae as Bb decreased survival and consequently the number of emerged adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aegypti and Cx. quinquefasciatus larvae and lower toxicity effect was observed on non-target species [23]. The https://doi.org/10.1371/journal.pone.0232172.g005 na = total number of mosquito larvae used per each species, 25 larvae per replicate, three replicates were carried out, five concentrations were tested; LC 50 = lethal concentration killing 50% of exposed organisms; LCL = 95% lower confidence limits; UCL = 95% upper confidence limits; χ2 = chi square ( � s = significant (p < 0.05)); df = degrees of freedom.…”
Section: Plos Onementioning
confidence: 97%
“…The In2Care mosquito traps manipulate the behavior of female mosquitoes by "skip oviposition" and finding cryptic breeding sites. At the same time, the B. bassiana spores will grow hyphae, feed upon the bodies, reproduce and kill the mosquitoes within 18 hours (Ragavendran et al, 2017).…”
Section: In2care Mosquito Trapmentioning
confidence: 99%